Politics and the sacred - Wydra, Harald (Cambridge University Press, 2015)
"This path-breaking book argues that practices of the sacred are constitutive of modern secular politics. Following a tradition of enquiry in anthropology and political theory, it examines how limit situations shape the political imagination and collective identity. As an experiential and cultural fact, the sacred emerges within, and simultaneously transcends, transgressive dynamics such as revolutions, wars, or globalisation"--